Agricultural Production amid Moisture Environments (International Journal of Innovative Research in Engineering & Management, 2021)
Rice production in Asia must increase continuously to feed  people. While the water shortage in rice cultivation in Asia  has yet to be completely evaluated, there is evidence that  water quality and availability decreases threaten the  sustainability of the irrigated rice system. Drought is one of  the major restrictions of high Rain-fed rice yields. Food safety  and environmental health in Asia must explore ways for  growing more rice with less water. This research examines the  whole rice production plan of the International Rice Research  Institute (IRRI), which includes genetics, breeding, and  integrated resource management. Irrigation techniques such as  saturated soil cultivation and alternative weathering and  dewatering will significantly reduce waste dumping while  increasing water yield. Another innovative method is being  investigated without sacrificing production to improve water  productivity. The C4 route is integrated into rice to increase  output per unit of transpired water, utilize genetic engineering  to improve dry tolerance and produce "aerobic rice" for good  and safe yields on unflooded soils.
Keywords: Drought; Fertilizer; Irrigation; Rainfall; Rice Production